(untitled) (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: The potential of schools as settings for health and physical activity promotion is well recognised. However, little is known about how schools collaborate with sports clubs to enhance physical activity. The purpose of this study was to investigate collaboration strategies between schools and sports clubs in Sweden over the past fve years. Methods: Using data from a Swedish nationwide registration system Generation Pep School tool, a total of 1,487 schools self-reported assessments between 2020 and 2024 were included. Responses were based on a 4-point scale (1 = no collaboration, 4 = a lot of collaboration with sports clubs). The data were analysed cross-sectionally using uni- and bivariate statistics. In addition, free-text responses from 1,125 schools were examined through thematic analysis. Results: The number of registrations per year was as follows: 2020 = 306, 2021 = 447, 2022 = 269, 2023 = 250, and 2024 = 215. Over the fve-year period, the extent of collaboration increased steadily, with the proportion of schools reporting ‘a substantial amount’ or ‘a lot’ of collaboration rising from 9% in 2020 to 30% in 2024 (p < 0.001). No statistically signifcant diﬀerences were observed between schools located in areas of low versus high socioeconomic status. Nevertheless, there was an observable trend: schools in higher socioeconomic areas were somewhat more likely to engage in collaboration (around 22%) compared to those in lower socioeconomic areas (around 12%). Interestingly, a larger proportion of schools in high-status areas reported no collaboration at all (44%) compared with schools in low-status areas (28%) in year 2024. Collaboration activities were bidirectional, involving both sports clubs visiting schools and pupils attending activities at sports clubs. In some cases, schools organised transportation directly from school to the sports clubs after the school day ended. Conclusion: A positive trend was observed in the increasing collaboration between schools and sports clubs over the fve-year period, with schools from low socioeconomic areas showing a particularly positive trend. Municipalities appeared to play a facilitative role in supporting and accelerating this development, and the collaborative eﬀorts were highly valued by both schools and sports clubs. Notably, the level of collaboration was consistent across areas with diﬀering socioeconomic status, indicating a degree of socioeconomic equity. Despite these advancements, there remains considerable potential to further enhance inter-sectoral cooperation to fully harness its health-promoting impact. Support/Funding Source: Foundation Kronprinsessan Margaretas Minnesfond.